Role of T Lymphocytes In Chronic Leukemia (Bangladesh Journal of Medical Science, 2017)
Functional immune cells are required for the prevention or resolution ofimmune-mediated disease , in particular T cells, including helper (CD4+; Th) or cytotoxic (CD8+; Tc) T cells. Th cells differentiate into Th1 or Th2 type cells, through production of inflammatory (IL-2, IFN-a) or anti-inflammatory (IL-4, TGF-ß) cytokines, respectively. Th cells also can differentiate into a third type of Th cells termeds Th17 type cells that produces IL-17 thereby mimicing the effects of Th1 cells. Th type cells can also differentiate under certain conditions into a regulatory (T-reg) type cell capable of secreting immunosuppressive cytokines such as TGF-ß and IL-10. This mini-review discusses the importance of T cell plasticity in regulating the nature of the immune cell responses seen in inflammatory diseases or cancer.Bangladesh Journal of Medical Science Vol.16(2) 2017 p.207-211